Analisis Pengaruh Media Sosial, Kepercayaan Konsumen, Dan Persepsi Harga Terhadap Keputusan Belanja Online Pada Siswa Kelas XI di SMK Kesehatan Surabaya - Senatriya Wahyu Ramadhan (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The current era is vast, especially in the field of business and marketing. Activities carried out with new and sophisticated technology, various information is obtained to facilitate online purchases. This study aims to determine the influence of social media, consumer trust, and price perception on online shopping decisions in grade XI students of SMK Kesehatan Surabaya. The sample used in this study was 110 respondents. The sampling technique used is non-probability sampling with purposive sampling method. The method used in this study is quantitative. The data analysis technique used to test the deep hypothesis is multiple linear regression analysis. Test results (F) show that social media, consumer trust, and price perception simultaneously have a significant influence on online shopping decisions. The results of the (t) test showed that social media and price perception had a partial significant effect smaller than 0.05, while consumer confidence did not have a significant effect on online shopping decisions because the significance value was greater than 0.05. The results of hypothesis testing on the price perception variable (X3) have the most dominant influence on online shopping decisions (Y).